PELAKSANAAN DAN PENGARUH SUPERVISI PENDIDIKAN DI SMA NEGERI 1 BANDUNG - Alya Syafira Khairunnisa; Balqis Najmi Aqila Putri Syaelah; Firda Nur Fauziah; Najma Sila Nayyara (Cahaya Ilmu Bangsa Institute, 2024)
At SMAN 1 Bandung, supervision is conducted by observing classes. The aim is to find teaching strengths and areas that need improvement. Based on the philosophy of postpositivism, this study used a descriptive qualitative approach. This approach allows an in-depth understanding of social phenomena in an educational context. Supervision was shown to assist teachers in professional development and evaluation through field observations, documentation analysis and structured interviews with the Vice Principal of the curriculum area. This study shows that collaboration between supervisors, teachers and related parties, such as parents, is essential to improve the quality of education. The results show that collaborative supervision methods can help implement education policies and improve the overall quality of learning.